The State Penghulu vs The Non-State Penghulu: The Validity and Implementing Authorities of Indonesian Marriage - Al Farabi (Justicia Islamica, 2020)
This research gives rise to the following questions: What is a valid marriage? Who holds the authority to grant it? Moreover, how does the existing authority(s) manifest among societies? This inquiry employs the socio-legal method by relying on doctrinal and empirical (ethnographic) approaches to answer these questions. The doctrinal approach applies to the first question and looks at how both the law and case law define a valid marriage. The ethnographic approach applies to the last two questions and looks at this law's functioning among society. As a result, this study reveals that the Marriage Law utilized registration to force people to comply with the law; otherwise, a religious marriage would not have the law force. An exemption applies only to marriages before enacting the Marriage Law, which is liable for retroactive validation. Later, this procedure is extended through case laws that apply isbath nikah (marriage validation) retroactively even to marriages after 1974 to accommodate unregistered marriages pervasive among society. The extended use of isbath nikah has made registration a mere administrative matter which no longer stands as a restriction to a religious marriage. Second, in practice, the judges’ lenient attitude toward isbath nikah has blurred the distinction between registered and unregistered marriages. The fluid distinction between these two provides a basis for Non-State Penghulus to exercise their authority alongside the State Penghulu. In this sense, the Non-State Penghulu appears as an alternative to the State Penghulu invalidating marriage among Muslims.